The RollingStone encyclopedia of rock and roll (Fireside, 1983)
The book includes over 1300 alphabetically listed entries, each of which contains basic biographical information as well as facts on group personnel and changes, album release dates, and an essay covering a performer's childhood, musical influences, first breaks, critical and commercial hits and misses, and information on his or her place in rock history; the first discography/personnel chronologies for group; information on singles and album, including Billboard chart positions and the Recording industry Association of America's gold and platinum certifications; more traditional, folk, country, pop, R&B and jazz Grammy awards through 1982; 150 historical photos; essays on African pop, studio technology, the evolution of reggae, and historical subjects such as rock on television, rock festivals, a list of the best-known one-hit wonders, rock and radio, rock dancing and more; definitions of 34 important musical terms, genres or phenomena from a capella and doo-wop to heavy metal, from the sound of New Orleans to disco, from new wave to no wave